2010
DOI: 10.4238/vol9-3gmr846
|View full text |Cite
|
Sign up to set email alerts
|

Genetic parameter estimates for buffalo milk yield, milk quality and mozzarella production and Bayesian inference analysis of their relationships

Abstract: ABSTRACT. Buffalo milk has excellent physical and chemical qualities as a consequence of the high percentage of constituents. This milk property is desirable for the dairy industry because it facilitates manufacture of mozzarella cheese. We estimated genetic parameters for milk yield, milk fat and protein and their effects on mozzarella cheese production using Bayesian inference. Using information from 4907 lactation records of buffaloes, genetic and non-genetic parameters were estimated for accumulated 305-da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 13 publications
1
11
1
Order By: Relevance
“…In this study, the estimated heritability for milk yield was lower than previously reported for buffaloes in Brazil: 0.30, 0.25, and 0.28 [ 11 , 25 , 26 ], respectively, but was higher than that reported in Italy 0.14 [ 21 ], Brazil 0.22 [ 27 ] and Colombia 0.22 [ 28 ].…”
Section: Discussioncontrasting
confidence: 89%
“…In this study, the estimated heritability for milk yield was lower than previously reported for buffaloes in Brazil: 0.30, 0.25, and 0.28 [ 11 , 25 , 26 ], respectively, but was higher than that reported in Italy 0.14 [ 21 ], Brazil 0.22 [ 27 ] and Colombia 0.22 [ 28 ].…”
Section: Discussioncontrasting
confidence: 89%
“…The repeatability of the models was low, preventing to predict future productions in the first lactations. Similar or higher estimates of repeatability were found by Ramos et al (2013) The heritabilities of the models MP270 (0.22) and MP305 (0.23) were similar to those found in the literature for buffaloes with adjustments for 270 days (Malhado et al, 2007;Rodrigues et al, 2010) and for 305 days (Aspilcueta-Borquis et al, 2010).…”
Section: Resultssupporting
confidence: 75%
“…On average, buffaloes have higher contents of milk fat than cattle. In buffaloes the percentage of milk fat ranges from 6.7 % to 12.0 % [ 11 , 50 52 ], while in cattle it ranges from 3.1 % to 4.5 % [ 53 , 54 ]. The difference in milk fat might be explained by a more efficient acetate metabolism to produce lipids in buffaloes, as the results suggest.…”
Section: Resultsmentioning
confidence: 99%